Animals and public health : why treating animals better is critical to human welfare - Akhtar, Aysha (Basingstoke : Palgrave Macmillan, 2012)
A compelling argument of how human health is adversely affected by our poor treatment of non-human animals. The author contents that in order to successfully confront the 21st century's health challenges, we need to broaden the definition of the word 'public' in public health to include non-human animals.
Keywords: Animal welfare; Health; Human-animal relationships